Coaxial nanofibers of chitosan–alginate–PEO polycomplex obtained by electrospinning. (20th August 2015) - Nista, Silvia Vaz Guerra; Bettini, Jefferson; Mei, Lucia Helena Innocentini
Highlights: Simultaneous electrospinning of alginate and chitosan was achieved. The ionic complex nanofibers based on alginate and chitosan was spontaneously formed. A coaxial (core–shell) structure of alginate and chitosan nanofibers was successfully obtained as evidenced by TEM. Abstract: Electrospinning of mucoadhesive membranes is a new and promising field of investigation in the pharmaceutical and biomedical area. The present study explored the electrospinning of two mucoadhesive polymers, chitosan and alginate, to form a core–shell type nanofibers for future applications as controlled drug delivery. Due to the charged functional groups present in these natural polysaccharides, they can complex to yield various nanodevices to be used in controlled release of several active ingredients. In this work, the core–shell type coaxial nanofibers formation was evidenced by the aid of transmission electron microscopy (TEM). Other characterization techniques as scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Infrared spectroscopy (FTIR) and X-ray diffraction (XRD), strongly suggest the formation of different molecular structures of the membranes obtained by the complexation of chitosan and alginate. Swelling rate and weight loss tests followed by SEM analyses confirmed that the nanofiber structure of these membranes were kept even after incubating them for 24 h in water. The results of this work confirmed that core–shell nanofibers made of chitosan and alginate polycomplex is possible to be obtained with success.